(untitled) (Student’s Journal of Health Research Africa, 2024)
Background The study aimed to correlate hysteroscopic findings with histopathological findings in women presenting with abnormal uterine bleeding and to study the accuracy of hysteroscopy in the evaluation of abnormal uterine bleeding Methods A prospective study was conducted in the Department of Gynecology at IGIMS, Patna from November 2021 to October 2023. A total of 58 patients who came with a history of abnormal uterine bleeding during this period were selected for the study. The hysteroscopic examination was done in all these patients post-menstrually, whenever possible, except in those cases where menstrual cycles were grossly irregular or patients came with continuous bleeding per vaginum. Endometrial biopsies were taken in the same sitting and sent for histopathological examination. Then correlation between findings on hysteroscopy and histopathological examination was done. Results Hysteroscopy revealed that 48.27% of patients had normal findings, while 51.73% had abnormalities. The most common abnormal hysteroscopic finding was hyperplasia (20.69%), followed by endometrial polyp (10.35%), myoma/myomatous polyp (6.86%), and endometrial carcinoma (5.18%). The histopathological examination showed 53.57% of patients had normal findings, with proliferative endometrium being the most common normal finding. Among abnormal histopathological findings, hyperplasia (16.07%) and endometrial polyp (8.93%) were prevalent. The accuracy of hysteroscopy in diagnosing normal endometrium, atrophic endometrium, and endometrial carcinoma was high, with a sensitivity of 100%. Conclusions Hysteroscopy allows direct visualization and biopsy of abnormal uterine bleeding. It can accurately diagnose normal and abnormal situations, although it may not detect hyperplasia as well as histology. The study emphasizes combining diagnostic methods to improve accuracy. Recommendations Whenever possible, hysteroscopy should be used to diagnose abnormal uterine bleeding. It permits direct visualization of the uterine interior. Diagnostic accuracy is improved with hysteroscopic biopsies. Hysteroscopic-histopathological correlations need further study to improve diagnostic methods.